Fever burden within 24 h after hematoma evacuation predicts early neurological deterioration in patients with intracerebral hemorrhage: a retrospective analysis - Wu, Fan; Xiong, Yu; He, Shi-ling; Wang, Xiao-hua; Chen, Xin-li; Chen, Wei-can; Huang, Qiao-mei; Huang, Xin-yue; Pan, Zhi-gang; Hu, Wei-peng; He, He-fan; Zheng, Feng (Frontiers in Neurology, 2023)
Background: Early neurological deterioration after hematoma evacuation is closely associated with a poor prognosis in patients with intracerebral hemorrhage. However, the relationship between body temperature after hematoma evacuation and early neurological deterioration remains unclear. Therefore, this study aims to explore the possible relationship between body temperature and early neurological deterioration in patients with intracerebral hemorrhage after hematoma evacuation. Methods: We retrospectively collected data from patients with cerebral hemorrhage at our institute between January 2017 and April 2022. The Student 's t-test, Mann-Whitney U-test, and χ 2 Test and Fisher 's exact test were used to analyze the clinical baseline data. A univariate logistic regression model was used to evaluate the association between the body temperature indices and early neurological deterioration. The predictive power was assessed Body temperature and END using the area under the Receiver Operating Characteristic (ROC) curve. The secondary outcome was a poor functional outcome.Results: Among 2,726 patients with intracerebral hemorrhage, 308 who underwent hematoma evacuation were included in the present analysis. A total of 82 patients (22.6%) developed early neurological deterioration. Univariate analysis showed that sex (p=0.041); body temperature at 6 h (p=0.005), 12 h (p=0.01), and 24 h (p=0.008) after surgery; duration of fever(p=0.008); and fever burden (p < 0.001) were associated with early neurological deterioration. Multivariate logistic regression showed that fever burden was independently associated with early neurological deterioration (OR=1.055 per ℃ × hour, 95%CI 1.008-1.103, p=0.020). ROC showed that fever burden (AUC=0.590; 95%CI: 0.514-0.666) could predict the occurrence of early neurological deterioration.Fever burden is associated with early neurological deterioration in intracerebral hemorrhage patients undergoing hematoma evacuation. Our findings add to previous evidence on the relationship between the fever burden and the occurrence of early neurological deterioration in patients with intracerebral hemorrhage. Future studies with larger sample sizes are required to confirm these findings.